Role of Health Simulation Training in Response to Pandemic Crises in General and COVID-19 Specifically - Malaekah, Haifaa M; Assaf, Wajdan Al; Alsofyani, Mohammad A; Aljahany, Muna; Boker, Abdulaziz (Archives of Clinical and Biomedical Research, 2022)
COVID-19 pandemic current status mandates a major role of healthcare in preventing the spread of infection besides treating infected patients. Health simulation training provides a practical role to improve the response to crises. This role involves the education and preparation of healthcare workers and the community while checking health system preparation in response to the pandemic crisis. The aim of this review is to describe the role of simulation in response to pandemic crises in general and the COVID-19 pandemic specifically. We seek to find and collect evidence that can be used to analyze what are the needs of this pandemic, describe how can simulation help in improving responses to the crisis, describe the major issues that can be faced when integrating simulation into programs and organizations, and specify the areas that need focus when conducting simulations. We conducted a literature review of available literature from 2004 to May 2020 to summarize the last evidence related to simulation and pandemic crisis.